Influence of nonalcoholic fatty liver disease severity on carotid adventitial vasa vasorum - León-Mengíbar, Josep; Sánchez, Enric; Herrerías, Ferrán; De La Fuente, Mari Cruz; Santamaría, Maite; Valdivielso, José Manuel; Bermúdez-López, Marcelino; Castro, Eva; Pallarés, Judit; Matias-Guiu, Xavier; Vilardell, Felip; Caixàs, Assumpta; et al. (Frontiers in Endocrinology, 2024)
INTRODUCTION: Nonalcoholic fatty liver disease (NAFLD) affects a quarter of the world's population and encompasses a spectrum of liver conditions, from non-alcoholic steatohepatitis (NASH) to inflammation and fibrosis. In addition, NAFLD also links to extrahepatic conditions like diabetes or obesity. However, it remains unclear if NAFLD independently correlates with the onset and progression of atherosclerosis. MATERIAL AND METHODS: This cross-sectional study aimed to explore the relationship between NAFLD severity, assessed via liver biopsy, and early atherosclerosis using adventitial vasa vasorum (VV) density. It included 44 patients with obesity (33 with steatosis, 11 with NASH) undergoing bariatric surgery. RESULTS: Results revealed no significant differences in adventitial VV density between steatosis and NASH groups, neither in the mean values [0.759±0.104 vs. 0.780±0.043, P=0.702] nor left-right sides. Similarly, carotid intima-media thickness (cIMT) did not vary between these groups. Additionally, no linear correlation existed between VV density and cIMT. Only gender showed an association with VV density. CONCLUSION: These findings suggest that NASH severity doesn't independently drive early atherosclerosis or affects cIMT. Gender might play a role in early atherosclerotic disease in NAFLD, impacting VV density and cIMT. This highlights the need to consider other risk factors when evaluating cardiovascular risk in NAFLD patients.